STUDY OF NAFLD DYNAMICS USING FIBROSCAN IN THE CONTEXT OF BARIATRIC SURGERY - Barno Kh. Shagazatova; Sitora Kh. Rakhimova (Central Asian Journal of Medicine, 2024)
This study is dedicated to evaluating liver condition in patients with obesity before and after bariatric surgery using the FibroScan method. Non-alcoholic fatty liver disease (NAFLD) is one of the most common causes of chronic liver diseases, and 12 to 14% of patients have an aggressive form of NAFLD known as non-alcoholic steatohepatitis (NASH). NASH can progress to liver fibrosis, cirrhosis, or liver cancer, especially in individuals with obesity and/or type 2 diabetes. The study included 44 patients treated in the endocrinology department of TMA and the Medion Family Hospital from 2022 to 2024. The patients were divided into two groups: gastric bypass (n=19) and sleeve resection (n=25). Biochemical and hormonal parameters, as well as lipid profiles, were assessed before and after surgery. The results showed significant improvement in lipid profiles and reduction in liver fibrosis 24 months after surgery, confirming the effectiveness of bariatric surgery in treating NAFLD and associated metabolic disorders.